Pengaruh Model Concept Sentence Berbantu Media Gambar terhadap Keterampilan Menulis Puisi Siswa SDN Kota Bengkulu - Rizki Dwi Prayogi; Abdul Muktadir; Wurdjinem Wurdjinem (Universitas Bengkulu, 2019)
The purpose of the research knew for influencing cooperative learning model in type concept sentence by using picture media in writing poem at V grade SDN Gugus IX Bengkulu. This research was quantitative. Reasearch Method used Quasy Experimental Research in design resarch The Matching Only Pretest-Posttset Group Design. The populations of the reasearch were students at V SDN Gugus IX bengkulu. Technique collecting data used cluster random sampling. The sample of the research was to group of work, consisted at VC SDN 82 Bengkulu (experimental class) and VA SDN 73 Bengkulu (Control Class). Research instrument used writing skill test of poem which gave pre test before teaching learning process and post test after teaching learning process. the data of the result could analyze by using descriptive analysis, test and T-test inferencial analysis. Data of the result knew the Mean of pre test at experimental class (58) and post test (79), while the Mean pre test at control class (57) and post test (73). The result T-test of post test on control group of experimental showed that the result of T-test 3,97 was more than T-test on significant 5% as 1,67 so Ha received and H0 refused. It means that the influencing of cooperative learning model in type concept sentence by using picture media in writing poem implemented at V grade SDN Gugus IX Bengkulu.